Do Kinetics of the Humoral Response to Cryptococcus neoformans Proteins during Murine Cryptococcosis Reflect Outcome? - Neuville, Segolene (American Society for Microbiology, 2000)
The kinetics of the humoral response to Cryptococcus neoformans proteins were studied in outbred mice infected with isolate NIH52D. Future nonsurvivors had earlier and stronger (i.e., more bands recognized) humoral responses than survivors. In addition, antibodies to a 56- to 60-kDa membrane antigen and to a 39- to 40-kDa cytosolic antigen were detected more frequently in samples from future nonsurvivors and from survivors, respectively (P < 0.05).